Makna Mendidik pada Kain Songket Silungkang Sumatera Barat - Budiwirman Budiwirman (International Conference on Languages and Arts, 2012)
This study aims to identify the symbolic significance of education in traditional clothing Silungkang West Sumatra. To identify the motif forms containing symbolic values ​​education in songket Silungkang, and analyze the educational values ​​inherent in Silungkang songket. To browse the educational symbolic values ​​contained in this Songket, with the basic elements that should be found according to the formulation of the problem. Types of research used ethnographic methods associated with qualitative research. That is, qualitative researchers are as a human instrument, serves to adjust the focus of research, selecting informants as data sources, gathering data, assessing the quality of data, analyze data, interpret data and make conclusions on the findings, and techniques of data analysis performed by analysis of the meaning of an interactive model , model analysis has three main types of component analysis, namely data reduction, data and conclusion / verification. Each researcher collected data to move on to the data / information collected is sufficient to answer the research issues and conclusions. The results obtained by the symbolic value of education is contained in songket Silungkang used by indigenous stakeholders (the prince and Bundo Kanduang) in the customary phrase says: smart (knowledgeable), know (knowledge), good (quality), which means the smart way , that the indigenous stakeholders. Means that stakeholders must know the practice of indigenous knowledge possessed, and which either means he has the expertise and wisdom in leading the community. The conclusion of this study is the significance of education in the prince clothes and Bundo Kandung a role model for people in the area Silungkang. Keywords: Symbolic, Songket, Culture.